The nutrient content of Plecostomus (Pterygoplichthys pardalis) flesh from Ciliwung River Jakarta, Indonesia - DEWI ELFIDASARI; AFINA PUTRI SHABIRA; IRAWAN SUGORO; LAKSMI NURUL ISMI (Nusantara Bioscience, 2019)
Abstract. Elfidasari D, Shabira AP, Sugoro I, Ismi LN. 2019. The nutrient content of Plecostomus (Pterygoplichthys pardalis) flesh from Ciliwung River Jakarta, Indonesia. Nusantara Bioscience 11: 30-34. One of the rivers in Jakarta, Indonesia that becomes the habitat of fish is Ciliwung River with Plecostomus as the dominant fish. The abundant number of Plecostomus in the Ciliwung river is utilized by the people living near the river basin area of Ciliwung River Jakarta as the main to produce food. As a source of animal nutrients, the contents of protein, fats, and carbohydrate in Plecostomus from Ciliwung River Jakarta has not been identified. The aforementioned condition has been the trigger to conduct this research aiming at identifying the contents of protein, fats, and carbohydrate in Plecostomus flesh from Ciliwung River Jakarta. The methods employed were Kjeldahl method to find out protein content, extraction method to test the fats, and by difference method to test carbohydrate with prior test of ashes using ash-drying method. The result shows that the smaller-sized Plecostomus with 18-23 cm in length had the highest contents of protein, fats, and ashes (50.0517%; 1.1261%; 1.1446%). Meanwhile, the medium-sized Plecostomus with 24-28.5 cm in length had the highest carbohydrate content (52.9905%). Statistical test using ANOVA with Duncan’s multiple range test shows that the contents of protein, fats, and carbohydrate in smaller, medium, and larger-sized Plecostomus do not show significant difference. The body length of Plecostomus from Ciliwung River Jakarta does not give significant effect on the contents of protein, fats, and carbohydrate in its flesh.